Reconstruction of post‐war social work: Experience from former Yugoslavia as an inspiration. (12th February 2020) - Hessle, Sven
Abstract : Immediately after the civil war among the nations of former Yugoslavia that took place 1992–1995, Swedish members of the social work faculty were recruited by UNICEF to support the organising of foster homes for war‐orphaned children. Around 20 projects, some initiated by UNICEF and others by SIDA (Swedish International Development Cooperation Agency) were also organised with Sarajevo University as the main location of the administration. At the request of the Parliament of Republika Srpska, a new school of social work was established at the University of Banja Luka. This was a successful project thanks to network collaboration among the faculties of social work in the former Yugoslavian nations and with academic contributions from universities from Sweden and Berlin. In this article, the two social welfare projects based in Sarajevo and Banja Luka are presented. Together with an accompanying group of experts, I found that an explorative mindset and an abductive approach were helpful tools in dialogues with our partners in the developing world.